When Music Takes Over in Film - Windisch, Anna K.; Tieber, Claus; Powrie, Phil (Palgrave Studies in Audio-Visual Culture,, 2023)
"This book reveals new insights into what happens when music is unconstrained by narrative. It is a brilliant read on what we thought we knew." - Kathryn Kalinak, Rhode Island College, USA "This collection is wonderfully rich in its range and astonishing in its revelation of the joyous and disturbing things musical moments can do." - Richard Dyer, King's College London, UK "The essays here will appeal to film scholars and music specialists alike." - Estella Tincknell, UWE Bristol, UK This open access collection deals with musical moments in film as one of the most pivotal and compelling issues of current film music research. Musical moments as defined by Amy Herzog occur when a musical number inverts the normal relationship between the image track and the soundtrack in a film in such a way that what we see is determined by what we hear. As one potential approach, this definition provokes a variety of perspectives to investigate the disruptive potential of these moments and numbers as a creative device in the production of audiovisual narratives. In this sense, the book responds to a need for an anthology that introduces students as well as scholars of cinema, musicology, media studies and cultural studies more broadly, to recent discourses in film music scholarship. The volume includes contributions by early career researchers as well as by established experts in the fields of musicology, film studies, media studies, and cultural studies, promoting cross-disciplinary collaboration in film music research. Anna K. Windisch is a film scholar who gained her PhD in Theatre, Film and Media Studies at the University of Vienna, Austria, and completed a postdoctoral position at the Austrian Academy of Sciences. Claus Tieber is Principal Investigator of the research project "Screenwriting musical numbers" in the Department of Theater, Film and Media Studies at the University of Vienna, Austria. Phil Powrie is Professor of Cinema Studies at the University of Surrey, UK, where he was Executive Dean of the Faculty of Arts and Human Sciences 2010-2015.